A revision of the genus Pochyta Simon, with descriptions of new species (Araneae: Salticidae: Thiratoscirtina) - Wesołowska, Wanda; Szűts, Tamás (Zootaxa, 2021)
Thiratoscirtina is an African endemic subtribe of aelurilline jumping spiders. Among the 18 genera belonging here, the genus Pochyta Simon, 1901 and its ten currently recognized species is yet to be revised, and the described species have been not studied from a taxonomical perspective. We examined all the species thought to belong here based on the type material. The limits of the genus are redefined. Pochyta moschensis Caporiacco, 1947 is proposed as the junior synonym of Natta horizontalis Karsch, 1879. Pochyta simoni Lessert, 1925 is transferred to the newly established genus Kibo gen. n., and a new combination Kibo simoni comb. n. is proposed for it. Both P. albimana Simon, 1902 and P. pannosa Simon, 1903 are proposed as a junior synonym of P. spinosa Simon, 1901, the type species. P. occidentalis Simon, 1902 is proposed as a junior synonym of P. pulchra (Thorell, 1899). Lectotypes are designated for Pochyta insulana and P. simoni. Seven new species are described: Pochyta aurantiaca sp. n. (♂♀), P. equatorialis sp. n. (♂♀), P. lucida sp. n. (♀), P. maddisoni sp. n. (♂♀), P. tendicula sp. n. (♂)—all from Gabon, P. konilokho sp. n. (♂) from Guinea, and P. minuta sp. n. (♀) from Nigeria. The yet unknown females of Pochyta fastibilis Simon, 1903, P. major Simon, 1902 and P. pulchra (Thorell, 1899) are described for the first time. New distribution data for some species are given.